(untitled) (Research, Society and Development, 2021)
Optimizing drug combination treatment has been an area of interest for a while, from the beginning with the emergence of the POMP regime. The ability to improve drug combinations for cancer treatment comes up against the possibility of several limitations, such as the lack of specificity of the drugs, generating systemic toxic effects, and also the great possibility of generating tumor cells resistant to the drugs. The development of nanooncology offers advances in new alternatives for the treatment of cancer, especially breast cancer. The strategy of using drugs combined in a nanocarrier for the treatment of breast cancer has proven to be quite effective, taking into account that breast cancer has long shown a good response with therapeutic combinations. In this work, we present a review of some examples of nanoformulations developed with the combination of drugs doxorubicin and/or paclitaxel aimed for the treatment of breast cancer. Also the future perspectives of nanotechnology in the drug combination.